Pengaruh Efektivitas Penggunaan E-Samsat Dan Pajak Progresif Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kantor Samsat Pembantu Renon - Yulinda, Ade Imma; Sudiana, I Wayan (Hita Akuntansi dan Keuangan, 2024)
The Samsat Office is a public service engaged in the payment of motorized vehicle tax (PKB). (PKB) is a type of regional tax whose authority is delegated to the provincial government as stipulated in Law Number 28 of 2009 concerning Regional Taxes and Regional Retribution. The largest state revenue is obtained through taxes, one of which is Motor Vehicle Tax (PKB). PKB is one aspect of Regional Original Income (PAD). However, there are many obstacles in paying PKB, including many people who are in arrears paying PKB, the level of public compliance in paying PKB is still low, and the community’s limitations in paying PKB during the Covid-19 pandemic. To overcome these problems an e-government system was created in which tax payment services are made online, namely through e-Samsat (Electronic One-Stop Manunggal Administration System). The purpose of this research is to determine the effect of the effectiveness of e-samsat and progressive taxes on taxpayer compliance. The theory in this study uses the theory task technology. The data used is primary data which will be obtained from distributing questionnaires. The number of samples used in this study were 97 respondents. The data collection technique used is in the form of a questionnaire. The analysis technique uses multiple linear regression. The results of this study found that the effectiveness of e-samsat and progressive tax simultaneously had a positive and significant effect on taxpayer compliance.